2002
DOI: 10.1248/bpb.25.1506
|View full text |Cite
|
Sign up to set email alerts
|

Production of Interleukin-1 Activity of Kupffer Cells from Mice Treated with the Acidic Mannan Fraction of Bakers' Yeast.

Abstract: Kupffer cells (KC), 1) resident macrophages of the liver, comprise a large and functionally important part of the mononuclear phagocyte system. Interleukin 1 (IL-1) is a monokine with a broad spectrum of biological activities, and its effects on a variety of cell types have been established. There are several reports that suggest that IL-1 could serve as a therapeutic tool for patients and mice with bacterial and fungal infections. [2][3][4][5][6] There is also accumulating evidence that lipopolysaccharide (LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…In line with this view, a number of studies have shown that S. cerevisiae [32,39] and constituents of its cell wall, such as mannans, cause fever that is accompanied by a putative increase in the plasma levels of TNF-a [15,40], IL-1b and interferon-c [40]. These data are corroborated by the findings of Okawa et al [41], who have shown that mannans increase IL-1b production in vitro, and of Rayhane et al [42] who have reported that the systemic administration of Cryptococcus neoformans does not increase TNF-a levels in murine brain. However, to our knowledge, no study has addressed whether the systemic administration of S. cerevisiae (or its derived mannans) increases IL-1b or TNF-a levels in the hypothalamus, a key cerebral structure for thermoregulation.…”
Section: Discussionsupporting
confidence: 59%
“…In line with this view, a number of studies have shown that S. cerevisiae [32,39] and constituents of its cell wall, such as mannans, cause fever that is accompanied by a putative increase in the plasma levels of TNF-a [15,40], IL-1b and interferon-c [40]. These data are corroborated by the findings of Okawa et al [41], who have shown that mannans increase IL-1b production in vitro, and of Rayhane et al [42] who have reported that the systemic administration of Cryptococcus neoformans does not increase TNF-a levels in murine brain. However, to our knowledge, no study has addressed whether the systemic administration of S. cerevisiae (or its derived mannans) increases IL-1b or TNF-a levels in the hypothalamus, a key cerebral structure for thermoregulation.…”
Section: Discussionsupporting
confidence: 59%
“…KC and sinusoidal endothelial cells (SEC) are equipped with mannose receptors (MRs), which are important for the recognition of foreign yeast that has mannan in the cell wall. 23 and play an important role in immune-mediated liver diseases such as liver inflammation and fibrosis. 24 Thus, the design of MR-specific carriers to deliver anti-inflammatory or antifibrotic compounds to these cells has great potential for therapy.…”
Section: ■ Introductionmentioning
confidence: 99%
“…KC and sinusoidal endothelial cells (SEC) are equipped with mannose receptors (MRs), which are important for the recognition of foreign yeast that has mannan in the cell wall . Both cell types are endowed with a high phagocytotic capacity and are part of the reticuloendothelial system (RES) and play an important role in immune-mediated liver diseases such as liver inflammation and fibrosis .…”
Section: Introductionmentioning
confidence: 99%